Analysis of Judge's Decision in a Human Trafficking Criminal Case (Case Study of Decision Number: 2045/PID.SUS/2023/PN SBY) - Rizal Pamungkas; Bastinto Nugroho; Sri Anggraini Kusuma Dewi (Journal on Education, 2025)
This research aims to analyze the judicial considerations and decision-making process in a human trafficking criminal case at the Surabaya District Court, specifically examining Case Number 2045/Pid.Sus/2023/PN Sby. Employing a normative legal research method with a juridical analysis approach, the study utilizes library research techniques to collect and examine secondary data from legal literature, court documents, and academic journals. The research focuses on exploring how judges determine legal considerations and sentencing in human trafficking cases, with particular attention to understanding the elements of human trafficking crimes and the application of substantive justice. The findings reveal that the court's decision-making process involves a comprehensive review of the indictment, evidence, witness testimonies, and consideration of both aggravating and mitigating factors. In this specific case, the defendant, Pendi Hermawan Bin Amung Suryadi, was found guilty of human trafficking under Article 2, Paragraph 1 of Law No. 21 of 2007 and sentenced to 3.5 years imprisonment and a fine of IDR 120,000,000. The study concludes that the judges' approach fulfilled the criteria of substantive justice by exploring community sense of justice beyond mere procedural formalities, thereby contributing to a more nuanced understanding of judicial decision-making in human trafficking cases.